Phytochemicals as novel agents for the induction of browning in white adipose tissue. Issue 1 (December 2016) - Azhar, Yusra; Parmar, Ashish; Miller, Colette; Samuels, Janaiya; Rayalam, Srujana
Abstract Obesity and its associated metabolic syndrome continue to be a health epidemic in westernized societies and is catching up in the developing world. Despite such increases, little headway has been made to reverse adverse weight gain in the global population. Few medical options exist for the treatment of obesity which points to the necessity for exploration of anti-obesity therapies including pharmaceutical and nutraceutical compounds. Defects in brown adipose tissue, a major energy dissipating organ, has been identified in the obese and is hypothesized to contribute to the overall metabolic deficit observed in obesity. Not surprisingly, considerable attention has been placed on the discovery of methods to activate brown adipose tissue. A variety of plant-derived, natural compounds have shown promise to regulate brown adipose tissue activity and enhance the lipolytic and catabolic potential of white adipose tissue. Through activation of the sympathetic nervous system, thyroid hormone signaling, and transcriptional regulation of metabolism, natural compounds such as capsaicin and resveratrol may provide a relatively safe and effective option to upregulate energy expenditure. Through utilizing the energy dissipating potential of such nutraceutical compounds, the possibility exists to provide a therapeutic solution to correct the energy imbalance that underlines obesity.